ANALISIS PENGGUNAAN METODE PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR DI SD NEGERI 010157 SEI MUKA - Sasmita, Vera (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
This study aims to analyze the use of learning methods in improving learning outcomes. This research uses quantitative analysis through descriptive analysis. The study was conducted on teachers at SD Negeri 010157 Sei Muka. The data collection tools using a questionnaire, research data were analyzed using descriptive analysis, from this study found that learning methods and student learning outcomes are in the medium category, as well as on the strong relationship between learning methods and student learning outcomes, thus it can be said that student learning outcomes can be improved by the use of appropriate and good learning methods by teachers in the learning process at school.